2021
DOI: 10.30996/persona.v10i1.4531
|View full text |Cite
|
Sign up to set email alerts
|

Stres akademik sebagai mediator kontribusi konsep diri akademik terhadap keterlibatan mahasiswa dalam perkuliahan daring

Abstract: Academic stress is something that is often experienced by students, especially with the change in the online learning system which is felt to put more academic pressure on students. This study aims to examine the contribution of academic self-concept to student engagement in online learning mediated by academic stress. Respondents (N = 356) students in Indonesia University of Education batch 2016 to 2019 completed questionnaire of The Academic Self-concept Scale (? = 0,74), The Online Student Engagement Scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
(35 reference statements)
0
4
0
3
Order By: Relevance
“…Although previous studies have found significant associations among teacher-student relationship, perceived social support, academic pressure, and academic engagement (Tsuno and Yamazaki, 2012;Qonita et al, 2021;Pham et al, 2022), we knew little about intrinsic relationship mechanism among them. To test the intrinsic relationship mechanism among teacher-student relationship, perceived social support, academic pressure, and academic engagement tended to be helpful for the interventions for improving university students' academic engagement, and therefore, the aim of the present study was to examine the association between teacherstudent relationship and academic engagement among university students, with particular attention on the mediating roles of perceived social support and academic pressure.…”
Section: Present Studymentioning
confidence: 92%
“…Although previous studies have found significant associations among teacher-student relationship, perceived social support, academic pressure, and academic engagement (Tsuno and Yamazaki, 2012;Qonita et al, 2021;Pham et al, 2022), we knew little about intrinsic relationship mechanism among them. To test the intrinsic relationship mechanism among teacher-student relationship, perceived social support, academic pressure, and academic engagement tended to be helpful for the interventions for improving university students' academic engagement, and therefore, the aim of the present study was to examine the association between teacherstudent relationship and academic engagement among university students, with particular attention on the mediating roles of perceived social support and academic pressure.…”
Section: Present Studymentioning
confidence: 92%
“…Dalam proses belajar mengajar, student engagement menjadi penting, dikarenakan adanya kemauan untuk mengikuti kegiatan sekolah dapat dilihat dari indikator kognitif, perilaku dan afektif dalam melaksanakan tugas pembelajaran (Chapman, 2003). Menurut Qonita et al (2021), mahasiswa menunjukkan perilaku lebih sering merasa lelah, bosan, malas hingga stres selama perkuliahan daring hal ini akan menyebabkan mahasiswa cenderung kurang terlibat dalam proses pembelajaran, kurangnya keterlibatan tersebut bisa dikarenakan persepsi negatif mahasiswa terhadap perkuliahan daring yang dirasa lebih membebani dan kurang efektif sehingga memengaruhi keterlibatan mahasiswa dalam perkuliahan. Sedangkan keterlibatan mahasiswa sangat penting untuk mendorong perilaku yang positif agar proses perkuliahan tetap berjalan efektif dan maksimal (Dixson 2015).…”
Section: Aunclassified
“…Mahasiswa dengan konsep diri akademis yang tinggi dapat mengetahui kemampuan akademisnya dengan baik sehingga mahasiswa dapat mencapai performa akademis yang optimal dan terdorong pada perilaku positif. Hal tersebut dapat diwujudkan melalui keterlibatan mahasiswa dalam tugas-tugas akademis, pengaturan pembelajaran, dan keterlibatan dalam menentukan strategi pembelajaran yang efektif dalam aktivitas akademis (Qonita, Dahlan, & Damaianti 2021).…”
Section: Metodeunclassified